ONCE AGAIN ABOUT «DURATIONAL TIME» IN ARTICLE 146 OF THE CRIMINAL CODE OF UKRAINE: TO BE OR NOT TO BE (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the problem of legislative definition of the content of the qualifying feature of the crime, provided for in Article 146 of the Criminal Code of Ukraine. It is about a long time, as an appropriate regulatory and legal criterion for assessing the increased degree of public danger of illegal deprivation of liberty or kidnapping of a person. The work analyses both scientific approaches to understanding a long time, and a number of court decisions where the issue was under juridical assessment. At the same time, it is shown that such a feature is interpreted in totally different way, and thus it creates a real problem in the correctness of understanding its true content and real use in the case of law enforcement activities. The author also expresses his own opinion on the calculation of the issues under consideration, which is based on the features of the selected criteria, with the help of which the appropriate assessment of a «long time» will acquire official and understandable grounds. It is emphasised that there is currently a legislative approach to the mere statement of the presence of the analysed feature within the framework of the relevant part of Article 146 of the Criminal Code of Ukraine cannot be considered correct. And primarily because of the significant questionability of using an evaluative concept with such a wide range of semantic load in a criminal-law norm.
Keywords: durational time; illegal deprivation of liberty; kidnapping